Request to change concrete grade C10 into C15 for lean/blinding concrete - BUCG-ABC Joint Venture (Brac University, 2023)
This record consists of general correspondence regarding request to change concrete grade C10 into C15 for lean/blinding concrete of BRAC University new campus project.